Effects of Low-Dose Antibiotics on Gut Immunity and Antibiotic Resistomes in Weaned Piglets - Hu, Qi; Liu, Cong; Zhang, Du; Wang, Ru; Qin, Linlin; Xu, Qin; Che, Lianqiang; Gao, Fei (Frontiers in Immunology, 2020)
Widespread antibiotic use increases the risk of livestock acting as potential reservoirs of antimicrobial resistance genes (ARGs) that may be transferred to human and animal pathogens. Particularly, maternal-infant transmission of antibiotics via breastmilk represents a great concern regarding infant health. In this study, we investigated the effects of 4-week low-dose antibiotic (LDA) treatment on the host immunity and antibiotic resistomes in weaned piglets. Transcriptomic analyses of ileum tissues revealed that the affected genes were largely enriched in innate immunity-related pathways. Significantly reduced protein expression of inflammatory factors, i.e., IFN-γ, IL-6 were observed. In addition, analyses of antibiotic resistomes identified a total of 1,021 ARGs related to 39 classes of antibiotics. The samples exhibited highly individual-specific diversity and no significant difference in the structure and diversity of ARGs and mobile gene elements (MGE) after LDA exposure for both colon and ileum samples. Despite of that, there were significant changes in the abundance of two transferrable ARGs [Erm(T) and tcr3] related to the antibiotics administered, implying an increased risk of transferrable antibiotic resistance. There was a significant change in the abundance of one pathogenic species after LDA exposure in the colon samples and one in the ileum samples, but there were no significant differences in the matched ARGs. Collectively, our findings reveal considerable changes in intestinal immunity-related genes, but minimal effects on gut antibiotic resistomes (ARGs and MGEs) in weaned piglets after 4 weeks LDA exposure. Our study provides a foundation for evaluating the longer-term cumulative effects of LDA use, especially the effects of maternal–infant LDA transmission, on antibiotic resistance and risks to infant health.